Relationship between Capital Requirement, Ownership Structure, and Financial Performance in Saudi Arabian Listed Companies - Alawi, Suha (Asian Economic and Financial Review, 2019)
Saudi Arabia’s capital market is highly concentrated due its regulators’ visible role. This study analyses the regulators’ role on the return on assets (ROA) and return on equity (ROE) to examine their impact on the capital market’s growth. Variables including institutional ownership, government ownership, foreign ownership and capital requirements were examined. Data was collected through the TASI Stock Market. The study included a panel dataset to observe 171 private and public listed companies by using the cross-sectional data from 2010 to 2014. Findings illustrated that company ownership concentration had a positive relationship in improving company’s performances, but foreign ownership had minimum significance. Similarly, ROA and ROE had a positive relationship with capital requirements. For various Saudi private and public listed companies, it is important to pay attention to capital market regulation as it plays a crucial role in improving company performance.